PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN (STUDI PADA WARUNK UPNORMAL SEMARANG) - Sumiyati, Sumiyati; Soliha, Euis (Proceeding SENDI_U, 2020)
This study aims to discuss and analyze product quality, price and location perceptions of customersatisfaction in Semarang Upnormal Warunk. The population in this study is Semarang Upnormal Warunkcustomers. The research method used is purposive sampling. The sample used was taken by 100 respondentswith a primary data collection method using a questionnaire. Data were analyzed using instrument tests,multiple linear analyzes and model tests.The results of the study prove the positive and significant product quality on customer satisfaction,positive and significant price perceptions on customer satisfaction, positive and significant location on customersatisfaction. The better the quality of the product, the more customer satisfaction increases. The better the priceperception the more customer satisfaction increases. The better the location, the more customer satisfactionincreases.